Preparation and Characterization of Urea with Coated-Urea Materials and their Performance to Reduce Ammonia Volatilization and Improve Crop Production - Junejo, Nasima (2011)
Urea is a widely used N fertilizer in the world. The rapid hydrolysis process of urea is responsible for high microsite pH and accumulation of NH4 in the soil. It caused NH3 emission from surface applied urea, resulting in poor N uptake and hazardous environmental effects. Urea can be more effective if an efficient method is devised to reduce NH3 losses. One of the approaches is to coat urea with biodegradable materials and urease inhibitors. The objectives of the study were; to prepare and characterize coated urea with biodegradable material and urease inhibitors; to evaluate the effects of the coated urea on NH3 losses, nitrogen transformations in soil and crop production. Laboratory, glasshouse and field studies were conducted to evaluate the physical and chemical properties of coated urea; to quantify the N transformation and ammonia volatilization loss on selected soil series and to determine yield and N uptake by plant from coated and uncoated urea. Six treatments of coated urea were prepared for the study labeled as; uncoated urea; palm stearin and Cu coated urea; agar and Cu coated urea; gelatin and Cu coated urea; Cu coated urea and Cu and Zn coated urea. The urea were coated with agar, gelatin, palm stearin, Cu and Zn by using fluidized bed coating machine. The coated urea was characterized for physical and chemical properties by using elemental analysis, FT-IR, TGA and SEM techniques. The results of study revealed that there were no significant changes were occurred in the properties of urea after coating. Laboratory evaluations of coated urea were carried out to quantify the N transformation and ammonia volatilization loss on three soil series named as; Munchong, Serdang and Holyrood. The urea coated treatments coated with combinations of agar, palm stearin and Cu had 20-23, 30-32 and 40 - 38 % lower microsite pH, NH4 and NO3 content in soil as compare to uncoated urea, respectively. In glass house study, Munchong soil series was used to grow the maize variety J-58. The plant were harvested after 8 weeks, followed by second planting on the same pots to determine residual effects of coated urea treatments on soil and plant. The coated and uncoated urea treatments, Triple super phosphate and potassium chloride was applied as fertilizer source of N, P and K at the rate of 100, 50, 100 kg ha-1 before the planting. After first harvesting, the second planting was done without application of N fertilizer. The results of both experiments revealed that 33- 40 % increase in N uptake and 40 - 60 % in dry matter yield of maize in the pot treated by coated urea with as compared to uncoated urea. However, the highest yield 26.50 and 26.45 g pot-1 was obtained from micronutrient coated urea at first harvest and from Agar and Cu coated urea at second harvest, respectively. To evaluate the effects of coated urea treatments under field condition, a pasture site (Guinea grass) was selected, harvested and fenced before application of fertilizer treatments. The duration of experiment was six months. During the experiment, the site was fertilized with urea treatments, TSP and KCl treatments at the rate of 217, 100 and 217 kg ha-1, respectively. And standardized agronomical operations were performed. The grass was cut two times at flowering stage to record dry matter yield. The soil and plant sample were analyzed for N, Cu and Zn content. The results showed 35 and 30 % improvement in N uptakes and crop production in UCuZn treated plots in at both harvestings, respectively. In addition, amendment of urea with multiple coatings has beneficial residual effects. It was concluded that coated urea can improve N uptake and reduce the ammonia losses. The urea coated with Biodegradable polymer and Cu had increased the residual effects of N.